Pelatihan Bussiness Model Kanvas Pada Sentra Industri Rumah Tangga Karasa Kabupaten Pinrang - Darwis; Ismayanti; Mutmainna; Rahman Abdul Rahman (Battuta-Jurnal Pemberdayaan Masyarakat, 2025)
This study aims to examine the direct effect of training effectiveness on business capital and training effectiveness on income, as well as the indirect effect of training effectiveness on income through the business capital of the Karasa traditional cake culinary industry. This research was designed using a quantitative exploratory approach. Data were collected through observation, interviews, and questionnaires. The population consists of culinary business actors in Pinrang Regency, with a non-probability sampling method and purposive sampling technique with a determined sample size of 55 respondents.  Data analysis was carried out using SmartPLS. Research Findings: Training is effective in increasing business capital and providing literacy to business actors to overcome capital limitations in business development. Training, however, cannot directly increase the income of business actors, so the type of training needs to be assessed for suitability to the needs so that training can effectively increase business income. Training indirectly increases income by paying attention to the accuracy of entrepreneurship training materials that produce outputs of increased knowledge and skills in overcoming obstacles in accessing capital.